Glyceryl trinitrate for acute intracerebral hemorrhage: results from the efficacy of nitric oxide in stroke (ENOS) trial, a subgroup analysis - Krishnan, Kailash; Scutt, Polly; Woodhouse, Lisa J.; Adami, Alessandro; Becker, Jennifer L.; Berge, Eivind; Cala, Lesley A.; Casado, Ana M.; Caso, Valeria; Chen, Christopher; Christensen, Hanna; Collins, Ronan; et al. (American Heart Association, 2015)
Background and purpose: The Efficacy of Nitric oxide in Stroke (ENOS) trial found that transdermal glyceryl trinitrate (GTN, a nitric oxide donor) lowered blood pressure but did not improve functional outcome in patients with acute stroke. However, GTN was associated with improved outcome if patients were randomised within 6 hours of stroke onset.